Observations on the Flora of Mandal Forest, Garhwal Himalaya, India - Singh, Gajendra; Naithani, H. B.; Rawat, G. S. (Indian Forester, 2009)
Systematic study on the vascular plants was conducted in Mandal Forest, located in the outer fringes of Kedarnath Wildlife Sanctuary, Western Himalaya. 575 species of angiosperms (364 genera and 101 families), 61 species of Ptridophytes (33 genera 21 families) and 4 species of Gymnosperms (3 genera 4 species) were recorded within about 10 km2 between 1500 m to 2900 m altitude amsl. The dominant families were: Poaceae (57), Asteraceae (44), Orchidaceae (36), Rosaceae (33), Lamiaceae (29), Cyperaceae (16) and Polygonaceae (16) in angiosperms and Polypodiaceae and Dryopteridaceae among the ferns. The study area forms only 0.28% of the total area of the erstwhile Chamoli District yet it harbours 28.44% of angiospermic flora, which makes it one of the interesting sites for the plant diversity in the District.